Pelvic Pain of Myofascial Origin in Women: Correlation with Lower Urinary Tract Symptoms - Sabrina Einig; Esther Ruess; Andreas Schoetzau; Kerstin Ayllon Bartet; Viola Heinzelmann-Schwarz; Francesco Vigo; Tilemachos Kavvadias (Advances in Urology)
Introduction. Women with lower urinary tract symptoms (LUTS) and high-tone pelvic floor often experience pain and have positive trigger points upon pelvic floor examination. However, the correlation of these findings has not yet been systematically examined and sufficiently understood. The aim of this cross-sectional study is to examine the correlation of pelvic myofascial pain with LUTS and pelvic floor tone. Materials and Methods. All participants filled a standardized pelvic floor questionnaire to assess LUTS, which consists of a total of 43 questions regarding bladder, bowel, and sexual function as well as prolapse symptoms. Myofascial trigger points in different muscle groups including pubococcygeus, iliococcygeus, and obturator as well as pelvic floor muscle tone were assessed using a standardized digital examination technique. Results. 110 women were included in the study. There was a significant correlation between pain in various muscle groups and LUTS as well as high-tone pelvic floor muscle. A significant correlation could also be found between high pelvic floor muscle tone and the overall questionnaire score (p<0.001) as well as the bladder function score (p<0.001) and various pain scores of the different groups. Individuals with high-tone pelvic floor were more likely to have more LUTS and higher pain scores. Conclusions. The existence of myofascial pelvic floor trigger points and high pelvic floor muscle tone seem to be reflective of pelvic floor symptoms, as assessed with a standardized pelvic floor questionnaire.